Faktor-Faktor Yang Mempengaruhi Kesuksesan Implementasi Sistem Informasi Studi Kasus Sistem Informasi Akademik (SIAKAD) STKIP Muhammadiyah Pringsewu Lampung - Susilo Hartono (Institut Informatika dan Bisnis Darmajaya, 2021)
This research used the success model of information system from Delone and Mc. Lean which has been modified based on the need and the situation at STKIP Muhammadiyah Pringsewu. The respondents were the first year students in the academic year 2012-2013 and the operators of SIAKAD. The number of the respondents were 196 students and 10 operators. The process of validity and reliability and the hyphotesa used Structural Equation Modeling (SEM). Which is analysed using Amos 20 software.The result of this research showed that from 5 hyphotesis which have been formulated, four of them were received. These hypothesis are the following : the quality of information influence the satisfying of the user ; the quality of the system influence the satisfying of the user; the trust influence the satisfying of the user; and the satisfying of the user influence the benefits of the SIAKAD. On the other hard, the quality of the service doesn’t has significant influence to the satisfying of the SIAKAD user. The success factors, which were resulted in this research, will be used as the suggestion and recomendation in the next SIAKAD development so that the sevice quality of SIAKAD to the students will increase. Keywords: Information Systems Success, DeLone and McLean Model, Structural Equation Modeling (SEM), Analysis of Moment Structures (AMOS).